2008
DOI: 10.1111/j.1365-2842.2008.01876.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dentinal tubule occlusion by dentifrice containing nano‐carbonate apatite

Abstract: This study evaluated the effects of the short-term use of a dentifrice containing nano-sized carbonate apatite (n-CAP) on the occlusion of the dentinal tubules using a scanning electron microscope (SEM) and an image analyser in vitro. One hundred human dentine specimens were wet ground with a silicone carbide papers and etched with 6% citric acid for 1 min to allow complete opening of the dentinal tubule. Specimens showing complete opening tubules were used as the baseline. The specimens were divided randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 15 publications
2
57
1
10
Order By: Relevance
“…Therefore, when mixed with distilled water, a large quantity of instantly formed MSNs easily entered the dentinal tubules and deposited on the walls of dentinal tubules. SEM observation results and statistical image analysis proved that MSNs not only almost completely occluded the dentinal tubules at the dentin surface, but also penetrated the dentinal tubules to a depth of about 105 μm, presenting results which were superior to the previous work [11][12][13] . The tubular occlusion efficacy of Ca 2+ / PO4 3− @MSNs group was similar to that of MSNs group at both the dentin surface and in the depth of dentinal tubules.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…Therefore, when mixed with distilled water, a large quantity of instantly formed MSNs easily entered the dentinal tubules and deposited on the walls of dentinal tubules. SEM observation results and statistical image analysis proved that MSNs not only almost completely occluded the dentinal tubules at the dentin surface, but also penetrated the dentinal tubules to a depth of about 105 μm, presenting results which were superior to the previous work [11][12][13] . The tubular occlusion efficacy of Ca 2+ / PO4 3− @MSNs group was similar to that of MSNs group at both the dentin surface and in the depth of dentinal tubules.…”
Section: Discussionsupporting
confidence: 49%
“…Length of the precipitate formed along the dentinal tubules from the dentinal surface to the bottom of precipitate was measured in at least 20 dentinal tubules for each sample. In addition, the degree of occlusion of the dentinal tubules on the dentinal surface was quantified using SEM and image analyses (Image-Pro PLUS 6.0, Media Cybernetics, Silver Spring, MD, USA) 13,20) . Three images were taken at a constant magnification of ×1000, with a 50-μm scale bar from the central portion of each sample (Schematic 1C).…”
Section: Evaluation Of Dentinal Tubule Occlusion Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Lee et al 34) reported that the dentinal tubule size increased as the exposure time of the dentin to the desensitizing toothpaste increased based on the experiment results regarding the deposited dentin, wherein a toothpaste containing nano-sized carbonate apatite was applied in a decalcification solution. It was found that the efficient time of the active ingredients of desensitizing agents was affected by the frequency of the brush strokes and the exposure time to the acid.…”
Section: Discussionmentioning
confidence: 99%